Dancing cocoa, Trinidad - Tucker (Davidson and Todd, Ltd., 2010)
A picture of a group of labourers walking on a large pile of cocoa beans while others turn them over with spades on a cocoa house so that the beans would dry evenly in the sun.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Cacao beans--Trinidad and Tobago; Working class--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago; Cocoa trade--Trinidad and Tobago; Cocoa houses